2017
DOI: 10.1007/s12028-017-0432-5
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of the Intracranial Pressure Threshold Value for the Initiation of Traumatic Brain Injury Treatment: A Xenon CT and Perfusion CT Study

Abstract: The cerebral circulation disturbance increased with the ICP value. We demonstrated the cerebral circulation disturbance at ICP values >20 mmHg. This study suggests that an ICP >20 mmHg is the threshold to initiate treatments. An active treatment intervention would be required for severe TBI when the ICP was >20 mmHg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Multiple studies have documented perfusion defects seen in TBI patients in a variety of sites throughout the brain [36,52,53,54,55,56,57]. Abnormal perfusion has been identified in the context of cerebral edema, extra-axial collections, and intracranial hypertension [58,59], see Figure 5, Figure 6 and Figure 7. One study has suggested that PCT may be able to distinguish whether an area of hypodensity on noncontrast CT is necrotic or viable, something that is not possible on noncontrast CT alone [60].…”
Section: Advanced Diagnostic Imaging Techniques In Traumatic Brainmentioning
confidence: 99%
“…Multiple studies have documented perfusion defects seen in TBI patients in a variety of sites throughout the brain [36,52,53,54,55,56,57]. Abnormal perfusion has been identified in the context of cerebral edema, extra-axial collections, and intracranial hypertension [58,59], see Figure 5, Figure 6 and Figure 7. One study has suggested that PCT may be able to distinguish whether an area of hypodensity on noncontrast CT is necrotic or viable, something that is not possible on noncontrast CT alone [60].…”
Section: Advanced Diagnostic Imaging Techniques In Traumatic Brainmentioning
confidence: 99%
“…It has a well-established role in the management of strokes and guides decisions on thrombolytic therapy by defining the area of ischaemic penumbra [ 5 , 6 , 7 , 8 ]. In studies in STBI patients, ICH has been associated with lower cerebral blood flow on CTP [ 9 ]. Abnormalities on CTP have also been shown to correlate with abnormalities in CPP and loss of cerebral autoregulation [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…When a patient with hemorrhagic stroke or TBI presents at a hospital emergency room, the clinician's priority is to forestall secondary tissue injury by preventing the immediate threats of systemic hypotension, hypoxia, and hypercarbia and by reducing the excess intracranial pressure. 112 In humans with hemorrhagic stroke or TBI, reducing intracranial pressure to levels at or below 20 mm Hg 34 is used as a proxy indicator for maintaining cerebral perfusion and oxygenation. 112 As reported previously, 25 immediate care for TBI is highly variable depending on the severity of the injury but also revolves around clinical management of intracranial pressure.…”
Section: Neurologic Injurymentioning
confidence: 99%